Feeding artery aneurysms associated with large meningiomas: case report and review of the literature. Issue 5 (May 2020) - Papadimitriou, Kyriakos; Rocca, Alda; Dunet, Vincent; Daniel, Roy Thomas
Abstract: Though brain tumors and intracranial aneurysms co-exist, the occurrence of feeding artery aneurysms with meningiomas are unusual. We describe here a large falcine meningioma that was associated with three feeding artery aneurysms of the anterior circulation. These aneurysms can be treated either by pre-operative endovascular therapy or during the meningioma surgery. The management strategy for these patients will depend on the clinical presentation, morphology and localization of these aneurysms with respect to the tumor. Abstract : Neuroscience; Neurology; Surgery; Neurosurgery; Clinical research; Intracranial meningioma, Intracranial aneurysm, Feeding artery aneurysm.